2022
DOI: 10.21203/rs.3.rs-2183516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TM4SF1 Upregulates MYH9 to Activate the NOTCH Pathway to Promote Cancer Stemness and Lenvatinib Resistance in HCC

Abstract: TM4SF1, a member of the transmembrane 4 superfamily, is crucial for both healthy and malignant human tissues. The significant function of TM4SF1 in the incidence and progression of cancer has been widely recognized in recent years. Although some achievements have been made in the study of TM4SF1, the effect of TM4SF1 on cancer stemness in hepatocellular carcinoma (HCC) and its molecular basis are yet to be reported. We found through abundant in vitro and in vivo experiments which the expression of TM4SF1 was p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…TM4SF1 is suggested to be a CSC membrane marker since its extracellular domain enhances CSC functions 20 . Similarly, TM4SF1 can increase cancer stemness in hepatocellular carcinoma by activating the NOTCH pathway through the upregulation of its downstream molecule MYH9 21 . Consistently, our results confirmed that sphere formation was significantly high in breast cancer cell lines with high TM4SF1 expression than that in cells with low expression.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…TM4SF1 is suggested to be a CSC membrane marker since its extracellular domain enhances CSC functions 20 . Similarly, TM4SF1 can increase cancer stemness in hepatocellular carcinoma by activating the NOTCH pathway through the upregulation of its downstream molecule MYH9 21 . Consistently, our results confirmed that sphere formation was significantly high in breast cancer cell lines with high TM4SF1 expression than that in cells with low expression.…”
Section: Discussionsupporting
confidence: 85%
“…TM4SF1 has oncogenic functions; for example, it facilitates proliferation, 13 migration, 34 angiogenesis, 16 self‐renewal ability, 20,21 and EMT, 16,35 and inhibits the apoptosis of cancer cells 36 . Our results support these findings by showing a decrease in metastatic potential and in vivo tumor growth after TM4SF1 depletion (Figure 5).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation